Intercultural collaboration by design - Murdoch-Kitt, Kelly M., author.
1 online resource
Keywords: "Intercultural Collaborations by Design introduces a framework for collaborating across cultures and learning to use multicultural perspectives to address pressing global issues. This handbook helps people work, learn, and teach across cultures. Through the activities highlighted in this book, virtual and intercultural teams will find a practical route for initiating and sustaining productive work across disciplinary and social barriers. Teams can craft a plan to achieve their goals by selecting the activities that best meet their needs and interests. First-person anecdotes from the authors demonstrate how the activities encourage teams to embrace diverse perspectives in order to create innovative solutions. With over 30 hands-on activities, this book will be of great interest to diverse teams from a variety of disciplines who want to enhance intercultural learning and co-working. Whether in the classroom or workplace, the activities are appropriate for a variety of collaboration contexts, without a need for background in art or design"--